Key foundations for high-quality corporate reporting : good practices of monitoring and enforcement, and compliance mehanisms (UN New YorkUS, 2014)
Describes the key elements that need to be considered when building efficient monitoring and enforcement systems for companies, audit firms and professional accountants. Highlights standards and guidance issued by international and regional bodies and selected national good practices. Discusses the main challenges faced by countries in their efforts to establish efficient mechanisms for the monitoring of compliance and enforcement.
Note by the UNCTAD Secretariat.